Dual-Frequency Circularly Polarized Truncated Square Aperture Patch Antenna with Slant Strip and L-Shaped Slot for WLAN Applications - Sorana Niyamanon; Rewat Senathong; Chuwong Phongcharoenpanich (My University, 2018)
This research proposes a dual-frequency circularly polarized truncated square aperture patch antenna with slant stripline and L-shaped slot for WLAN applications. In the antenna design, the parameters were optimized and the WLAN-enabled dual-frequency (2.4 and 5.8 GHz) antenna was realized. Simulations were subsequently carried out for the impedance bandwidth (S11) < −10 dB, axial ratio (AR) ≤ 3 dB, optimal gain, and bidirectional radiation pattern. To validate, an antenna prototype was fabricated and the experiments were undertaken. The simulated and experimental results are in good agreement. In essence, the proposed WLAN-enabled dual-frequency circularly polarized antenna is most suited for applications in the vertically and horizontally elongated areas, including in the tunnel, train carriage, and buildings.
Keywords: Aperture (computer memory); Antenna Design and Analysis